2021
DOI: 10.1101/2021.03.30.437704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence analysis of SARS-CoV-2 in nasopharyngeal samples from patients with COVID-19 illustrates population variation and diverse phenotypes, placing the in vitro growth properties of B.1.1.7 and B.1.351 lineage viruses in context

Abstract: New variants of SARS-CoV-2 are continuing to emerge and dominate the regional and global sequence landscapes. Several variants have been labelled as Variants of Concern (VOCs) because of perceptions or evidence that these may have a transmission advantage, increased risk of morbidly and/or mortality or immune evasion in the context of prior infection or vaccination. Placing the VOCs in context and also the underlying variability of SARS-CoV-2 is essential in understanding virus evolution and selection pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous data indicated that Victoria/01/202040 grew with a small plaque phenotype and lower titer compared to more contemporary variants including Variants of Concern (VOCs), that grew to higher titres with larger or mixed plaque morphologies 17 . The later virus isolates contained the P323L and D614G substitutions in NSP12 and the spike protein, respectively, as the dominant viral genome sequence, as well as other changes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous data indicated that Victoria/01/202040 grew with a small plaque phenotype and lower titer compared to more contemporary variants including Variants of Concern (VOCs), that grew to higher titres with larger or mixed plaque morphologies 17 . The later virus isolates contained the P323L and D614G substitutions in NSP12 and the spike protein, respectively, as the dominant viral genome sequence, as well as other changes.…”
Section: Resultsmentioning
confidence: 99%